Representatives of Lamiaceae Lindl. Family in Collection of Non-Traditional Aromatic Plants of M. M. Gryshko National Botanical Garden of NAS of Ukraine - Kovtun-Vodyanytska, Svitlana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
In this study discussed taxonomic composition of family of Lamiaceae Lindl., which are represented in the collection of non-traditional aromatic plants in M.M. Gryshko National Botanical Garden of NAS of Ukraine. In article offered the characteristic of unconventional introduced species of three genera such as: Nepeta argolica Bory & Chaub., Pycnanthemum tenuifolium Schrad. and Clinopodium menthifolium (Host) Stace. The biological, morphological features, rhythms of development and methods of plant reproduction under the conditions of introduction are indicated. Collecting og plant material of investigated plants and forming of experimental collections of non-traditional aromatic plants was caried out according to scientific recomendations of Bazilevskaya and Maurin (1982, 1986). Investigashions of plants have been conducted according to Rakhmetov (2006) and Bulakh (2010). The useful properties of these plants for humans, for example, their medicinal properties are described. Analize of literature reviews showed that all investigated plants have characterized by content of biological active compounds such as flavonoids, saponins, glycozides, organic acids, tannins, vitamins, carotene etc. This fact justifies widely use of group of these plants in folk medicine.